Ảnh hưởng của oligome dầu lanh epoxy hóa (OELO) đến tính chất cơ học của polyme epoxy. Phần 1. Ảnh hưởng của OELO đến tính chất cơ lý của màng và hệ số tập trung ứng suất tới hạn KIC của epoxy epikote 828 - Trung, Đặng Hữu; Ninh, Trần Hải; Diệu, Trần Vĩnh; Bích Thủy, Nguyễn Thị; Yến Oanh, Đoàn Thị (Vietnam Journal of Chemistry, 2014)
Epoxy resins are considered as one of the most important classes of thermosetting polymers for many industrial applications, but unfortunately they are characterized by a relatively low toughness. In this work, oligomer of epoxidized linseed oil (OELO) was used as a modifier for epoxy polymer. Different contents of OELO are evaluated for effecting on the most of mechanical properties of the epoxy resin. The fracture toughness of epoxy resin significantly increased by 64.4 % from 1.46 MPa.m1/2 to 2.40 MPa.m1/2 just by adding 6 phr (part per hundred of resin) OELO. Impact strength, cupping and scratch properties of polymer films significantly increased 96.4 %, 115 % and 260 %, respectively with content 10 phr OELO in compositions. Keywords: Fracture toughness, epoxy resin, cyanethyldiethylenetriamine, epikote 828, epoxidized linseed oil.